2021
DOI: 10.1136/bmjopen-2020-043315
|View full text |Cite
|
Sign up to set email alerts
|

Increasing use of CT requested by emergency department physicians in tertiary hospitals in Western Australia 2003–2015: an analysis of linked administrative data

Abstract: ObjectiveThis study aimed to examine trends in number of CT scans requested by tertiary emergency department (ED) physicians in Western Australia (WA) from 2003 to 2015 across broad demographic and presentation characteristics, anatomical areas and presented symptoms.DesignAn observational cross-sectional study over study period from 2003 to 2015.SettingLinked administrative health service data at individual level from WA.ParticipantsA total of 1 666 884 tertiary hospital ED presentations of people aged 18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Interestingly, the highest growth of CT use was observed among ED presentations in the semi-/nonurgent category (+256%), particularly from 2012 onward. Although the growth coincided with major health reforms happening in Australia in 2012 (National Emergency Access Target and Activity-Based Funding Model) discussed in a previous study, 11 other changes in practice may also explain the growth. For example, there is increasing appreciation of the unreliability of plain x-ray in line with increasing evidence that standard plain radiography can miss at least 50% of all cervical fractures.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Interestingly, the highest growth of CT use was observed among ED presentations in the semi-/nonurgent category (+256%), particularly from 2012 onward. Although the growth coincided with major health reforms happening in Australia in 2012 (National Emergency Access Target and Activity-Based Funding Model) discussed in a previous study, 11 other changes in practice may also explain the growth. For example, there is increasing appreciation of the unreliability of plain x-ray in line with increasing evidence that standard plain radiography can miss at least 50% of all cervical fractures.…”
Section: Discussionmentioning
confidence: 64%
“…[7][8][9][10] In Australia, a recent study found that the use of CT in tertiary (teaching) hospital EDs increased from 81 to 200 per 1,000 presentations with injury between 2003 and 2015. 11 Compared to nonionizing radiation imaging techniques and plain X-ray, CT scanning is a relatively high-radiation-dose diagnostic imaging technique and carries a small but nonnegligible absolute long-term risk to the patient of radiation-induced malignancy. 12 Despite improved technology leading to significant dose reduction for individual scans, its increasing use has attracted attention from the public, media, researchers, and health care providers about the health impacts caused by increasing radiation exposure to the population.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of consistent increase of readmissions and decrease in LOS across any, multiple and repeat CT also implies system changes, which could potentially be explained through changes in the Australian health system change, for example, the National Health Reform and Activity Based Funding Model (ABFM). 45 Financial reasons based on clinical activities within a hospitalisation could be linked to an earlier patient discharge (shorter LOS) to distribute activities across different hospitalisations for the same patient. In a systematic review and meta-analysis, Palmer et al 46 found that ABFM can cause an increase in readmission and a decrease in LOS, both of which were found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) utilization in the emergency department (ED) has been increasing globally over the years [ 1 , 2 ]. Iodinated contrast media (ICM) administration during contrast-enhanced CT (CECT) in the ED is crucial for the accurate diagnosis of acute conditions such as aortic dissection and pulmonary embolism [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%